2021
DOI: 10.1021/acs.orglett.1c01813
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Coupling Reactions of Monosubstituted Tetrazines

Abstract: A Ag-mediated Pd-catalyzed cross-coupling method for 3-bromo-1,2,4,5-tetrazine with boronic acids is presented. Electronic modification of the 1,1′-bis(diphenylphosphine)ferrocene (dppf) ligand was found to be crucial for good turnover. Using this fast method, a variety of alkyl-, heteroatom-, and halide-substituted aryland heteroaryl-tetrazines were prepared (29 examples, up to 87% yield).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
4
10
1
Order By: Relevance
“…This is in stark contrast to the reports by Amatore, and Grushin and Alper, respectively, which demonstrated that catalytically active Pd(0) complexes were only formed in the presence of H 2 O. A reasonable explanation for the decreased yields is the in situ formation of Ag 2 O, which in prior reports by our group was found to be an inferior mediator for the reaction . On the other hand, conclusive evidence for the involvement of Pd­(II) bisaryl complexes in the generation of the Pd(0) species was obtained when exchanging the 4-F-Ph-B­(OH) 2 for the less reactive C 6 F 5 -B­(OH) 2 .…”
contrasting
confidence: 99%
See 3 more Smart Citations
“…This is in stark contrast to the reports by Amatore, and Grushin and Alper, respectively, which demonstrated that catalytically active Pd(0) complexes were only formed in the presence of H 2 O. A reasonable explanation for the decreased yields is the in situ formation of Ag 2 O, which in prior reports by our group was found to be an inferior mediator for the reaction . On the other hand, conclusive evidence for the involvement of Pd­(II) bisaryl complexes in the generation of the Pd(0) species was obtained when exchanging the 4-F-Ph-B­(OH) 2 for the less reactive C 6 F 5 -B­(OH) 2 .…”
contrasting
confidence: 99%
“…Similar intermediates have been observed in previous experiments and during the preparation of the scope involving other challenging boronic acids (see SI). Taken together, this experimental evidence corroborates the hypothesis that increasingly electron-poor substrates suffer from decreased reductive elimination rates during precatalyst activation and product formation, which in turn would result in diminished yields and hence the limitation of the scope. Since reductive elimination rates were shown to be faster for electron-poor complexes, this effect would be in line with the reported success of the electron-poorer ligand dppf-CF 3 over its parent compound dppf. , Hence, Pd­(dba) 2 was established as a viable Pd(0) precursor for the process, which removed the necessity for the reduction of Pd­(II) (Scheme B). In situ generation of Pd 0 L n (dppf-CF 3 ), followed by cross-coupling of tetrazine 1 with 2 in the presence of 1.0 equiv.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…[37] We therefore selected the 3-position of acridine orange for installing a tetrazine moiety while maintaining the dimethylamino group at the 6-position. As previously observed for aryl tetrazines, [38,39] DFT calculations predicted PINK to be a planar molecule (Scheme 1). Upon intercalation, this co-planarity should result in cofacial alignment of the 5-vinyl and tetrazine groups to facilitate a highly rapid reaction between PINK and VdU residues (Figure S2, Supporting Information).…”
supporting
confidence: 70%